2019
DOI: 10.1007/s13205-019-1626-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of silicon nanoparticles in agriculture

Abstract: The beneficial effects of silicon and its role for plants are well established; however, the advantages of silicon nanoparticles over its bulk material are an area that is less explored. Silicon nanoparticles have distinctive physiological characteristics that allow them to enter plants and influence plant metabolic activities. The mesoporous nature of silicon nanoparticles also makes them good candidates as suitable nanocarriers for different molecules that may help in agriculture. Several studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(191 citation statements)
references
References 47 publications
4
179
0
8
Order By: Relevance
“…The future prospective of this research may extend to the biotechnology field, which aims to explore the molecular bases of plant defense mechanisms. Implementing nanoparticle-mediated targeting of biomolecules [134] in such research would be useful for developing new cultivars resistant to various environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The future prospective of this research may extend to the biotechnology field, which aims to explore the molecular bases of plant defense mechanisms. Implementing nanoparticle-mediated targeting of biomolecules [134] in such research would be useful for developing new cultivars resistant to various environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Also, others showed the effectives role of nanomaterial fertilizers on plant growth and productivity [21]. On the other hand, several research works have been carried out to prove the positive impact of silica nanoparticles to the crops, such as Rastogi et al (2019) who reported the benefits of SiO 2− NPs on physiological features of the plant in which that, they allow them to enter plants and affect its metabolic activities [71]. The same group also claim that the mesoporous nature of silica nanoparticles can also direct them to be good applicants as nano carriers for several molecules that may support in agriculture [71].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies are there to overcome fertilizer/pesticide induced health effects. Rastogi et.al, 2019 reported use of silicone nanoparticles can provide green and eco-friendly alternatives to various chemical fertilizers without harming nature [91]. It has been reported that selenium (Se) application decreases Cd uptake [75].…”
Section: Recommendationsmentioning
confidence: 99%